10.1: High Mobility Self‐Aligned Top‐Gate Oxide TFT for High‐Resolution AM‐OLED. Issue 1 (1st July 2013) - Morosawa, Narihiro; Nishiyama, Masanori; Ohshima, Yoshihiro; Sato, Ayumu; Terai, Yasuhiro; Tokunaga, Kazuhiko; Iwasaki, Junji; Akamatsu, Keiichi; Kanitani, Yuya; Tanaka, Shinji; Arai, Toshiaki; Nomoto, Kazumasa
Abstract: High mobility and highly reliable self‐aligned top‐gate oxide TFTs were developed using the aluminum reaction method. Al diffusion to the oxide semiconductor and homogenization of the oxygen concentration in the depth direction after annealing was confirmed by laser‐assisted atom probe tomography. The high mobility of the top‐gate TFT with a‐ITZO channel was demonstrated to be 32 cm 2 /Vs. A 9.9‐inch diagonal qHD AM‐OLED display was fabricated using a five‐mask backplane process to demonstrate an applicable solution for large size and high‐resolution AM‐OLEDs.